Expression of fibroblast growth factor-8 and regulation of cognate receptors, fibroblast growth factor receptor-3c and-4, in bovine antral follicles - Buratini, J.; Teixeira, A. B.; Costa, I. B.; Glapinski, V. F.; Pinto, MGL; Giometti, I. C.; Barros, C. M.; Cao, M.; Nicola, E. S.; Price, C. (Bio Scientifica Ltd, 2005)
Paracrine cell signaling is believed to be important for ovarian follicle development, and a role for some members of the fibroblast growth factor (FGF) family has been suggested. In the present study, we tested the hypothesis that FGF-8 and its cognate receptors (FGFR3c and FGFR4) are expressed in bovine antral follicles. RT-PCR was used to analyze bovine Fgf8, Fgfr3c and Fgfr4 mRNA levels in oocytes, and granulosa and theca cells. Fgf8 expression was detected in oocytes and in granulosa and theca cells; this expression pattern differs from that reported in rodents. Granulosa and theca cells, but not oocytes, expressed Fgfr3c, and expression in granulosa cells increased significantly with follicle estradiol content, a major indicator of follicle health. Fgfr4 expression was restricted to theca cells in the follicle, and decreased significantly with increasing follicle size. To investigate the potential regulation of Fgfr3c expression in the bovine granulosa, cells were cultured in serum-free medium with FSH or IGF-I; gene expression was upregulated by FSH but not by IGF-I. The FSH-responsive and developmentally regulated patterns of Fgfr3c mRNA expression suggest that this receptor is a potential mediator of paracrine signaling to granulosa cells during antral follicle growth in cattle.